Formation of French Personalist Thought as Philosophical Response to Civilizational Crisis - Gorban, Richard (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
In this article, the author substantiates that Personalism, formed in the 1930-s in France due to the endeavors of Maritain, Mounier and Berdiaiev, originated not like one of the forms of Modernism, which was a manifestation of the crisis, but as a philosophical response to the crisis phenomena at the turn of the 19th century. This crisis was bound with the utter secularization of all spheres of life in concomitance with anti-clerical and antichristian moods. The idea of Catholic revival kindled in the minds of the philosophers-personalists, who realized the civilizational scale of modern decline of social and cultural institutions, dehumanization and depersonalization in society and searched for a set of rules of thumb to surmount the crisis. Against the backdrop of the decay of philosophical thought, French personalists countered the idea of personalistic civilization, the structure and spirit of which are aimed at personal self-fulfillment, with the fascist and communist concepts, anti-personalistic by nature, that were inspired by the philosophy of Nitzsche and Marks and aspired not just to dominate the world but conduct civilization mission. It is evident that a signature plank of French Personalism is its pedagogical vector, determined by the development of personalistic concept of a human being, that would become part of the training program for the educational process within the framework of civilization. Its other feature, that had ramifications in the modern world, is the efforts exerted by philosophers of religion to unify peoples, both the faithful and atheists, around common personalistic values. The ideas of French personalists were implemented into social policy of the Catholic Church and became philosophical foundations of refocusing of Christian theology, declared at the second Vatican Council as an extremely important task of the course of the Catholic renewal (aggiornamento).